FLUKTUASI HARGA IKAN CAKALANG (Katsuwonus pelamis L) SEGAR DI PASAR Ã¢â‚¬Å“BERSEHATIÃ¢â‚¬Â KOTA MANADO PROPINSI SULAWESI UTARA - Olvie V. Kotambunan (Universitas Sam Ratulangi, 2013)
Abstract This study aims to determine the cause of fluctuations in the market price of tuna